Tinjauan Terhadap Kemiskinan di Indonesia: Penyebab dan Upaya Penanggulangan Kemiskinan - Pratiwi, Anggie Erna; Wulandari, Desi; Hutabarat, Emma Triadelina; Silaban, Surta Tiodora (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Poverty is a complex problem that has a wide impact on Indonesian society. This article aims to explore the main causes of poverty and its alleviation efforts based on a literature review of various journals and reports. Factors such as inequality in income distribution, disparities between regions, and internal individual factors also influence the level of poverty in Indonesia. This article also discusses various government programs that have been implemented to reduce poverty and the challenges faced in their implementation. In addition, entrepreneurship is discussed as one of the important pillars in driving economic growth and the welfare of rural communities.